2010
DOI: 10.1002/hep.23818
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Enriched Transcription Factors Regulate MicroRNA-122 That Targets CUTL1 During Liver Development

Abstract: MicroRNA-122 (miR-122) is a liver-specific microRNA whose expression is specifically turned on in the mouse liver during embryogenesis, thus it is expected to be involved in liver development. However, the role of miR-122 in liver development and its potential underlying mechanism remain unclear. Here, we show that the expression of miR-122 is closely correlated with four liver-enriched transcription factors (LETFs)-hepatocyte nuclear factor (HNF) 1a, HNF3b, HNF4a, and CCAAT/enhancer-binding protein (C/EBP) a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
253
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(266 citation statements)
references
References 36 publications
(77 reference statements)
11
253
1
1
Order By: Relevance
“…These observations suggest that miR-122 may play an essential role in the regulation of hepatocyte differentiation and liver development. Direct evidence that miR-122 might be involved in liver development was first provided by Xu et al (2010), who showed in mice that four liver-enriched transcription factors including hepatocyte nuclear factor (HNF) 1α, HNF3β, HNF4α and CCAAT/enhancer-binding protein (C/EBP)α bind to miR-122 promoter and activate miR-122 expression. The increase of miR-122 leads to down-regulation of its target CUTL1, a transcriptional repressor of genes specifying terminal differentiation in hepatocytes, thereby contributing to differentiation of hepatocytes (Xu et al, 2010).…”
Section: Mir-122 In Liver Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations suggest that miR-122 may play an essential role in the regulation of hepatocyte differentiation and liver development. Direct evidence that miR-122 might be involved in liver development was first provided by Xu et al (2010), who showed in mice that four liver-enriched transcription factors including hepatocyte nuclear factor (HNF) 1α, HNF3β, HNF4α and CCAAT/enhancer-binding protein (C/EBP)α bind to miR-122 promoter and activate miR-122 expression. The increase of miR-122 leads to down-regulation of its target CUTL1, a transcriptional repressor of genes specifying terminal differentiation in hepatocytes, thereby contributing to differentiation of hepatocytes (Xu et al, 2010).…”
Section: Mir-122 In Liver Developmentmentioning
confidence: 99%
“…Direct evidence that miR-122 might be involved in liver development was first provided by Xu et al (2010), who showed in mice that four liver-enriched transcription factors including hepatocyte nuclear factor (HNF) 1α, HNF3β, HNF4α and CCAAT/enhancer-binding protein (C/EBP)α bind to miR-122 promoter and activate miR-122 expression. The increase of miR-122 leads to down-regulation of its target CUTL1, a transcriptional repressor of genes specifying terminal differentiation in hepatocytes, thereby contributing to differentiation of hepatocytes (Xu et al, 2010). A subsequent study further showed that as transcriptional stimulators, HNF6 and its paralog Onecut2 promote the expression of miR-122 which is required for proper progression of hepatocyte differentiation.…”
Section: Mir-122 In Liver Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Quantitative analyses of miRs have demonstrated higher and dynamic expression in various developmental stages of liver during the fetal period. 35 MiR-30 is crucial for liver development and it is upregulated during later developmental stages, influencing known regulators of hepatic function, including epidermal growth factor receptor.…”
Section: Hepatic Micrornas and Liver Diseasementioning
confidence: 99%
“…[37][38][39] It is highly expressed in hepatocytes due to its liver specific transcriptional regulation by hepatic nuclear transcription factors 34,40 and is elevated in most hepatic diseases including hepatitis C virus (HCV) and hepatitis B virus (HBV) infections as well as alcohol and drug-induced liver injury, HCC and NAFLD. 13,14,[37][38][39][40][41][42][43][44][45] There are four miR-122 binding sites in the HCV genome 42 and miR-122 may promote viral replication by direct interaction with seed-sequencebinding to two target sites, S1 and S2, in the 5 0 -UTR of the HCV genome resulting in HCV-RNA genome stabilization and enhanced viral RNA abundance.…”
Section: Microrna-122mentioning
confidence: 99%